KONTRIBUSI KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU - Iis Aisah (Universitas Majalengka, 2019)
This research is motivated by the low performance of teachers, aims to examine descriptively about competence, work environment, and teacher performance and examine verification about the effect of competence and environment on teacher performance both partially and simultaneously. The research method used is descriptive and verification. The population consisted of 51 Sumedang Group SLB teachers with a proportional stratified random sampling technique. Data sources in this study are primary and secondary data with correlation and regression analysis techniques. Descriptive research results prove that teacher competence and the work environment are in good condition, but there are still weaknesses in certain aspects. Verification analysis results prove that teacher competence and work environment influence teacher performance both partially and simultaneously.